Représentations du temps et de l’espace en science-fiction : du roman à l’écran - Orlane Glises de la Rivière (ReS Futurae)
Tarkovski has adapted two science-fiction books: Solaris writing by Stanislas Lem and Stalker from Arkadi and Boris Strougatski. The books deal with the presence of an alien intelligences to which humans are confronted: they don’t understand who or what it is. Tarkovski offers a mystical and spiritual vision in his movies. We will analyze the spatial cinematographic dimension in his films, which complete the literary spatiality. In addition, Tarkovski proposes a new vision of temporality through cinema. We will asking how the director does bring a new interpretation to these books through cinema. How does it transmit his own vision of space and time? We will see that this notions are essential in the genre of science-fiction.